Polski cyceronianista Andrzej Frycz Modrzewski a łacina kościelna - Malinowska, Jolanta (Vox Patrum, 1988)
An article entitled "The Polish ciceronianist - Andrzej Frycz Modrzewski and the church Latin", deals with the problem of a semantic evolution of some political terms used by Modrzewski in his work "De Republica emendanda".